Impact of CdTe thin film thickness in ZnxCd1−xS/CdTe solar cell by RF sputtering. (1st March 2019) - Hossain, Mohammad Sharafat; Rahman, Kazi Sajedur; Karim, Mohammad Rezaul; Aijaz, Mohammed Omer; Dar, Mushtaq Ahmad; Shar, Muhammad Ali; Misran, Halina; Amin, Nowshad
Highlights: CdTe thin films are grown at variable thickness by sputtering. CdTe thin film analysis is done for structural, morphological and optical properties. Fabrication of Znx Cd1−x S/CdTe solar cells is done where x = 0.2 for Zn. Best cell efficiency of 8.79% achieved for 3.5 μm thick CdTe. Abstract: This paper presents the impact of thickness of RF sputtered CdTe thin film as an absorber layer through structural and optical characterization in Znx Cd1−x S/CdTe solar cells at lower concentration of zinc (Zn). The crystallographic, morphological and optical properties of CdTe thin film fabricated on top of bare soda-lime glass were elucidated by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and ultraviolet (UV) spectrophotometer. XRD spectra shows that crystallinity increases in thicker samples and the CdTe (1 1 1) diffraction peak intensity centered at 23.825° increases with the increase of film thickness confirming the zinc blend structure of CdTe thin film. The window layer Znx Cd1−x S was fabricated with optimum deposition conditions by co-sputtering of ZnS and CdS. The complete cell was fabricated by RF magnetron sputtering with the cell configuration of glass/FTO/Znx Cd1−x S/ZnTe/Ag. With the increasing thicknesses of CdTe the cell efficiency increases with the highest efficiency of 8.79% for 3.5 μm of CdTe. This paves the way of novel window of ZnCdTe for smoothening the junction mismatches in hetero-junction CdTe thin film solar cells.